Strategi Perencanaan Program Sponsorship untuk Meningkatkan Efektivitas Pameran oleh PT Nusaraya Asa Pameran (ASA Exhibitions) - Angelica, Talita Alicia; Setyawan, Heri; Wardhani, Annisa (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2024)
Sponsorship program planning is a key element in the success of an exhibition. This study aims to explore the sponsorship planning strategy implemented by PT Nusaraya Asa Exhibition (ASA Exhibitions) in the context of the 2024 Indonesia Beauty Influencers Summit event. Through a qualitative approach with observation, interview, and documentation methods, the research results show that the planning process involves several stages, including preparing a sponsorship proposal, creating a database of potential sponsors, communicating and sending proposals, following up, negotiating, and dealing. This study also identified several challenges in sponsorship program planning, including obstacles in bartering products that do not match the value of the booth being sold and the lack of interest of potential sponsors in sponsorship packages that are considered too expensive. These findings provide insight into best practices and challenges faced in sponsorship planning, as well as suggestions for improving the effectiveness of future sponsorship programs. Keywords: Sponsorship, Planning, Sponsorship Program, Exhibition